2014
DOI: 10.1007/s10803-014-2125-7
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Potentiated Startle in Fragile X Syndrome

Abstract: Social avoidance and anxiety are prevalent in fragile X syndrome (FXS) and are potentially mediated by the amygdala, a brain region critical for social behavior. Unfortunately, fMRI investigation of the amygdala in FXS is limited by the difficulties experienced by intellectually impaired and anxious participants. We investigated the relationship between social avoidance and emotion-potentiated startle, a probe of amygdala activation, in children and adolescents with FXS, developmental disability without FXS (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 61 publications
1
2
0
Order By: Relevance
“…In men with the FMR1 premutation, attenuated amygdalar activation has also been seen during an emotion-matching task, as well as impaired startle potentiation while viewing fear faces (Hessl et al, 2011). Consistent with these neuroimaging studies, emotion-potentiated startle, a probe of amygdala activation, was found to be reduced in children and adolescents with FXS compared to a typically developing control group (Ballinger et al, 2014).…”
Section: Discussionsupporting
confidence: 59%
“…In men with the FMR1 premutation, attenuated amygdalar activation has also been seen during an emotion-matching task, as well as impaired startle potentiation while viewing fear faces (Hessl et al, 2011). Consistent with these neuroimaging studies, emotion-potentiated startle, a probe of amygdala activation, was found to be reduced in children and adolescents with FXS compared to a typically developing control group (Ballinger et al, 2014).…”
Section: Discussionsupporting
confidence: 59%
“…FMRP is an RNA binding protein that functions as a translational repressor at synapses (Antar and Bassell, 2003 ; Bagni and Oostra, 2013 ; Darnell and Klann, 2013 ; Sidorov et al, 2013 ). FMRP is important for learning and memory, and its absence is associated with the characteristic features of FXS, including intellectual disability, cognitive impairments and behavioral problems, autism spectrum disorders (ASD), Attention Deficit Hyperactivity Disorder (ADHD), seizure, in addition to hyper-responsiveness to sensory stimuli, hyperactivity, impulsive behavior, gaze aversion and shyness (Hull and Hagerman, 1993 ; Hagerman, 2002 ; Smith et al, 2012 ; Schneider et al, 2013 ; Ballinger et al, 2014 ; Machalicek et al, 2014 ; Maurin et al, 2014 ; Thurman et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Anxiety disorders are common in individuals with FXS, with 70 to 80% having some form of anxiety [107]. Selective serotonin reuptake inhibitors (SSRIs), like sertraline are very effective for this purpose [65,99].…”
Section: Anxiety Symptomsmentioning
confidence: 99%